Aerosol‐driven increase in Arctic sea ice over the middle of the twentieth century. Issue 14 (28th July 2017) - Gagné, Marie‐Ève; Fyfe, John C.; Gillett, Nathan P.; Polyakov, Igor V.; Flato, Gregory M.
Abstract: Updated observational data sets without climatological infilling show that there was an increase in sea ice concentration in the eastern Arctic between 1950 and 1975, contrary to earlier climatology infilled observational data sets that show weak interannual variations during that time period. We here present climate model simulations showing that this observed sea ice concentration increase was primarily a consequence of cooling induced by increasing anthropogenic aerosols and natural forcing. Indeed, sulphur dioxide emissions, which lead to the formation of sulphate aerosols, peaked around 1980 causing a sharp increase in the burden of sulphate between the 1950s and 1970s; but since 1980, the burden has dropped. Our climate model simulations show that the cooling contribution of aerosols offset the warming effect of increasing greenhouse gases over the midtwentieth century resulting in the expansion of the Arctic sea ice cover. These results challenge the perception that Arctic sea ice extent was unperturbed by human influence until the 1970s, suggesting instead that it exhibited earlier forced multidecadal variations, with implications for our understanding of impacts and adaptation in human and natural Arctic systems. Key Points: Two newly updated observational data sets indicate an increase in sea ice concentration in the eastern Arctic between 1950 and 1975 Model simulations using a large ensemble indicate that this increase was driven by increasing anthropogenic aerosols Consistent results are found with a subset of simulations from models of the CMIP5 ensemble that include aerosols indirect effects